Compressive properties of Napier (Pennisetum Purpureum) filled polyester composites. (15th March 2016) - Fartini, M. S.; Abdul Majid, M. S.; Ridzuan, M. J. M.; Amin, N. A. M.; Gibson, A. G.
Abstract : The effects of Napier filler on the compressive properties of an unsaturated polyester polymer were studied at various temperatures. Polyester resins with Napier filler contents of 1, 3 and 5wt-% were prepared using three different mixing methods (hand mixing, water shaker bath and hot plate stirrer). Static uniaxial compression tests were conducted to investigate the compressive stress–strain response, failure mechanisms and damage characteristics of the neat and Napier filled polyester. The results show that the elastic modulus and compressive strength of the Napier modified polyesters were improved, without significantly reducing the failure strain, by increasing the Napier content. The samples prepared by the hot plate stirrer method yielded the highest compressive strength. The strength and Young's modulus of the Napier filled polyester decreased as the temperature increased. This result suggests that the Napier filler introduced additional mechanisms of energy absorption, improving the compressive properties.